White-nose syndrome pathology grading in Nearctic and Palearctic bats - Pikula, Jiri; Amelon, Sybill K.; Bandouchova, Hana; Bartonička, Tomáš; Berkova, Hana; Brichta, Jiri; Hooper, Sarah; Kokurewicz, Tomasz; Kolarik, Miroslav; Köllner, Bernd; Kovacova, Veronika; Linhart, Petr; et al. (PLOS ONE, 2017)
While white-nose syndrome (WNS) has decimated hibernating bat populations in the Nearctic, species from the Palearctic appear to cope better with the fungal skin infection causing WNS. This has encouraged multiple hypotheses on the mechanisms leading to differential survival of species exposed to the same pathogen. To facilitate intercontinental comparisons, we proposed a novel pathogenesis-based grading scheme consistent with WNS diagnosis histopathology criteria. UV light-guided collection was used to obtain single biopsies from Nearctic and Palearctic bat wing membranes non-lethally. The proposed scheme scores eleven grades associated with WNS on histopathology. Given weights reflective of grade severity, the sum of findings from an individual results in weighted cumulative WNS pathology score. The probability of finding fungal skin colonisation and single, multiple or confluent cupping erosions increased with increase in Pseudogymnoascus destructans load. Increasing fungal load mimicked progression of skin infection from epidermal surface colonisation to deep dermal invasion. Similarly, the number of UV-fluorescent lesions increased with increasing weighted cumulative WNS pathology score, demonstrating congruence between WNS-associated tissue damage and extent of UV fluorescence. In a case report, we demonstrated that UV-fluorescence disappears within two weeks of euthermy. Change in fluorescence was coupled with a reduction in weighted cumulative WNS pathology score, whereby both methods lost diagnostic utility. While weighted cumulative WNS pathology scores were greater in the Nearctic than Palearctic, values for Nearctic bats were within the range of those for Palearctic species. Accumulation of wing damage probably influences mortality in affected bats, as demonstrated by a fatal case of Myotis daubentonii with natural WNS infection and healing in Myotis myotis. The proposed semi-quantitative pathology score provided good agreement between experienced raters, showing it to be a powerful and widely applicable tool for defining WNS severity.